Synthesis of Evaluations in South Sudan: Lessons Learned for Engagement in Fragile and Conflict-Affected States. Issue 1 (1st January 2020) - Cochrane, Logan
Abstract : South Sudan is one the largest recipients of official development assistance. Given the complexity of the operational environment, there is a need to learn from the lessons gained to-date. This article seeks to enable better-informed decision making based on a synthesis from humanitarian and development evaluation reports, which offer insight for engagement in other fragile and conflict-affected states. Experimental methods were utilised to identify evaluation reports. The synthesis finds that projects would be better designed if they allocated time and resources to obtain additional information, integrated systems thinking to account for the broader context, and engaged with the gendered nature of activities and impacts. Implementation can be strengthened if seasonality is taken into account, if modalities are more flexible, and if a greater degree of communication and collaboration between partners develops. Sustainability and long-term impact require that there is a higher degree of alignment with the government, longer-term commitments in programming, a recognition of trade-offs, and a clear vision and strategy for transitioning capacities and responsibilities to national actors. While actors in South Sudan have been slow to act on lessons learned to-date, the lessons drawn from evaluation reports in South Sudan offer direction for new ways forward, many of which have been concurrently learned by a diverse set of donors and organisations.